Disentangling the contributions of ocean ranching and net-pen aquaculture in the successful establishment of Chinook salmon in a Patagonian basin - Di Prinzio, Cecilia Yanina (2015)
The presence of Chinook salmon in Patagonia is an example of a successful invasion by a Pacific salmon species. The combination of historical records and genetic data can help to determine the origin of invasive / introduced species and allow the identification of the sources and dispersal process. We analyzed the genetic structure of Chinook salmon in the Futaleufú River (Pacific slope basin of Patagonia) using single nucleotide polymorphism genotypes and a recently described baseline dataset of native North American Chinook salmon populations. Our results revealed that Chinook salmon established in the Futaleufú River have high levels of within-population genetic diversity compared with populations from across the native range. Based on genetic similarity and historical reports, our results indicate that the Futaleufú population was first established by colonizing fish derived from the Lower Columbia River Basin, imported into Chile for ocean ranching purposes during the 1970s and 1980s, and afterward it was strongly supplemented by escaped fish from net pen aquaculture that used broodstock imported during the 1990s from various sources, including the California Central Valley (via New Zealand), the Middle Oregon Coast, and Vancouver Island. The higher incidence of fish derived from the most recent introductions in our sample suggest that the contribution of escaped salmon from these posterior stockings on establishment success must have been particularly strong because included different sources. Subsequent admixture and hybridization among these multiple independent source stocks is likely responsible for the high level of standing genetic variation, which may be facilitating local adaptation and augmenting the opportunity for successful invasion and further colonization.